2002
DOI: 10.1080/01913120290104683
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Combined Treatment with Cisplatin and Gentamicin in the Guinea Pig: Glomerular Injury Findings

Abstract: The drugs cisplatin and gentamicin are given consecutively to various cancer patients suffering from infections. Little information exists about the ultrastructural alterations of kidney glomeruli caused by treatment with these drugs. Renal glomeruli of guinea pigs treated with cisplatin alone and in combination with gentamicin were studied by transmission electron microscopy. The findings revealed foci of damage induced by cisplatin and especially by cisplatin/gentamicin in all glomerular components: glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…In a rat model of cisplatin nephrotoxicity, damage to glomerular capillaries, including endothelial cells, has been described previously (Kohn et al, 2002). Caspases and calpain are independent mediators of cisplatin-induced endothelial cell necrosis in vitro (Dursun et al, 2006).…”
mentioning
confidence: 99%
“…In a rat model of cisplatin nephrotoxicity, damage to glomerular capillaries, including endothelial cells, has been described previously (Kohn et al, 2002). Caspases and calpain are independent mediators of cisplatin-induced endothelial cell necrosis in vitro (Dursun et al, 2006).…”
mentioning
confidence: 99%
“…Approaches to reduce the incidence and severity of cisplatin-associated toxicity are under intensive investigation indicate that. (9,12,18,24) Cisplatininduced nephrotoxicity, ototoxicity, and neurotoxicity have been associated with potential microvascular damage, (17)(18)(19) and previous animal experiments and clinical reports have demonstrated that vascular factors (20)(21)(22) contribute to renal dysfunction following exposure to cisplatin. The mechanisms underlying these troublesome vascular-injury-associated side-effects, which are regarded as crucial in the pathogenesis of tissue damage, might involve the proliferation inhibition effect of cisplatin on endothelial cells in vitro (18,32,33) and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-stimulated ICAM-1 induction in endothelial cell will promote or reinforce leukocyte/endothelium interactions as we observed in vivo, which in turn may contribute to the cisplatin-associated toxicities. First and foremost, enhanced leukocyte/endothelium interactions may directly or/ and indirectly induce vascular damage, (17)(18)(19) which may be associated with cisplatin-induced nephrotoxicity, ototoxicity and neurotoxicity. Once adhered to the endothelium, neutrophils may then release proteases, toxic oxygen metabolites and vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such vascular toxicity has been manifested by increased von Willebrand factor plasma levels as well as an enhanced intima-media thickness of the carotid artery (8). In addition, cisplatin has the potential to induce ototoxicity and toxicity towards renal, peripheral sensory and autonomic nervous systems, potentially attributed to cisplatin-caused microvascular damage (9)(10)(11). Ca 2+ plays an important role in the regulation of vascular tone, which is generally relatively constant.…”
Section: Introductionmentioning
confidence: 99%